Standardization of Cob Drying Technology for Maintaining Vigour Potential of Maize Seeds - V MANONMANI; S SUBITHRA; S AMBIKA (Seed Research, 2026)
An investigation was carried out with maize to evaluate the optimum stage of cob maturity, duration of drying and drying temperature for maintaining the germination and vigour potential of maize seeds in storage. The maize cobs harvested at different maturity stages viz. 95-100 days after sowing, 100-105 days after sowing and 105-110 days after sowing were subjected to mechanical drying at various temperatures viz., 40°C, 45°C, 50°C and 55°C along with sun drying. To optimize the duration of drying, the cob moisture content was recorded at every two hours interval up to the safe seed moisture content of 12%. The maize cobs subjected to various drying temperatures of 40°C and 45°C taken lesser duration for drying compared to sun drying (50 h). However, the minimum duration of drying was recorded in 50°C (24 h) followed by 55°C (18 h). Maize cobs harvested at 100-105 days after sowing and dried at 40°C outperformed other drying treatments by recording higher viability,germination and vigour with low mechanical injury.